PHYSIOTHERAPEUTIC INTERVENTION IN TREATING TEMPOROMANDIBULAR DISORDERS: A SYSTEMATIC REVIEW - Silva, Samara Emanuela Coelho da (2018)
Introduction: The Temporomandibular Joint (TMJ) is formed by a set of anatomical structures that establish a connection between the temporal bone and the mandible. This joint is susceptible to pathological variations leading to disorder such as temporomandibular dysfunction. Temporomandibular dysfunction (TMD) is defined by the pathological alteration that impairs the temporomandibular joint (TMJ), having potential to affect the masticatory muscles and the stomatognathic system. The physiotherapeutic intervention aims to ameliorate musculoskeletal pain, reduce inflammation and spasms, gain or maintain range of motion, recover the function of the masticatory system and promote the re-education of the patient to improve the quality of life. Objective: In this way the objective of this study was to analyze the scientific evidences about the physical therapy treatment in the temporomandibular disorder. Methods: Electronic searches were carried out in PubMed, Lilacs and Scielo databases to identify the scientific articles indexed and published in the years 2011 to 2018. Twenty articles were selected after analysis and 11 were used. Results: The results obtained in this study , it is noted that the physiotherapeutic resources bring good results in patients with TMD, reducing pain and increasing range of motion. Conclusion: According to the results presented in this study, it was concluded that the physiotherapeutic resources have good results in patients with TMD.